Analisis Efektivitas Penggunaan Modul Kuliah, Chatgpt, Dan Github Copilot Dalam Pembelajaran Pemrograman Aplikasi Mobile - Isnardi Isnardi; Meldi Putra (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2025)
This research aims to analyze the effectiveness of the use of lecture modules, ChatGPT, and GitHub Copilot in mobile application programming learning. A descriptive quantitative method was employed with the distribution of questionnaires to 52 students. The results showed that ChatGPT and GitHub Copilot are effective in completing practical tasks, while the lecture modules remain important as theoretical references. The combination of these three tools results in a more efficient and in-depth learning process.Keywords: Lecture Modules, ChatGPT, GitHub Copilot, Mobile Learning, Effectiveness